Students’ Perceptions of An Exemplary Online ESP Teacher: A Mixed-Methods Study - Gayatri, Putri; Ruminar, Hafida; Lintangsari, Alies Poetri (Inspiring: English Education Journal, 2024)
The shift from traditional to online teaching and learning during the COVID-19 pandemic has caused various hurdles. As indicated by many reports, both students and the teachers experienced dissatisfaction and met challenges during the teaching and learning process. Amidst several students’ dissatisfaction with the online delivery of various subject, a report on teaching and learning experience revealed the exceptional performance of an English for Specific Purposes (ESP) teacher named Ms. Sarah (a pseudonym) as recognised by the student. The researchers then did a mixed method study to identify the specific features of Ms. Sarah's teaching that students found engaging and pleasurable. The data, both quantitative and qualitative, was gathered by administering closed and open-ended questionnaires to a total of 38 students who were enrolling in Ms. Sarah's class. The findings indicated that Ms. Sarah's online ESP lesson was well-received. All students (100%) expressed confidence in Ms. Sarah's competence to deliver online ESP instruction. A majority of over 80% of the participants indicated their endorsement for other teachers to embrace Ms. Sarah’s instructional approach, while a total of 97.37% conveyed their intention to join Ms. Sarah's other courses in the upcoming semester. This paper also presents a more detailed explanation of the rationales why students appreciate Ms. Sarah's online class. Besides, considering SLA theory and cultural dimension was also found to contribute to the effective online instructions. Ms Sarah's approach in conducting online ESP course might be an invaluable resource for ESP teachers looking to improve their online teaching strategies. Keywords: Online instructions, ESP, SLA, Cultural dimensions